Mine-to-smelter integration framework for regional development of porphyry copper deposits within the Chilean context. (2nd January 2022) - Wilson, R.; Perez, K.; Toro, N.; Parra, R.; Mackey, P. J.; Navarra, A.
ABSTRACT : Trends toward the widespread use of electric vehicles and renewable energy sources all point to continued growth in copper demand. This demand will be met mainly by new primary copper production, with recycling expected to contribute significantly to copper supply. Significant quantities of copper ore are presently mined from porphyry deposits in which typically, near-surface copper oxides are recovered hydrometallurgically by leaching, solvent extraction and electrowinning, whereas the deeper copper sulphides are only amenable to milling followed by pyrometallurgical processing and electrolytic refining. The Chilean copper porphyries together are the largest group of operating copper mines and are likely to remain so into the future. However, several of these deposits are forecast to show increasing levels of arsenic-bearing minerals, such as enargite. As mature copper mining districts exhaust the near-surface oxides and higher-grade sulphides, individual mines will need to adjust their operations accordingly. However, it is considered that due to such changes, re-engineering efforts might be more economically coordinated across several mines, to collectively handle the evolving ore feeds. The present paper adapts a discrete event simulation (DES) approach to support mine-to-smelter integration within porphyry copper districts. Sample computations are presented that are loosely based on the Chilean context.